1990
DOI: 10.1103/physrevb.41.11837
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic locking and friction

Abstract: %'hen solid bodies contact and slide against each other, the frictional phenomenon occurs. The origin of the related frictional force is studied by assuming the existence of two clean crystal surfaces, which follows the current experimental trends. This study theoretically clarifies the atomistic origin of the frictional force intrinsically generated by the molecular interactions between the constituent atoms of solids, but not the force extrinsically generated by surface asperities, the existence of foreign a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
370
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(377 citation statements)
references
References 14 publications
4
370
1
2
Order By: Relevance
“…28 Qualitatively, the conclusions agree with those of the simpler models. However, based on numerical calculations for ␣-iron, the authors conclude that nonadiabatic motion is unlikely to occur even in metallic systems.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…28 Qualitatively, the conclusions agree with those of the simpler models. However, based on numerical calculations for ␣-iron, the authors conclude that nonadiabatic motion is unlikely to occur even in metallic systems.…”
Section: Introductionsupporting
confidence: 80%
“…23,27,28 The possibility has been suggested that two incommensurate surfaces can slide over one another without any friction. 23,27,28 Some studies predict that this could happen even in metallic systems. 28 In order to investigate the effect of interfacial mismatch on the frictional properties, a series of simulations have been performed for a system like the one in Fig.…”
Section: B Cu"111… Tip/cu"111… Surface Nonmatching Surfacesmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] The interlayer interaction is known to be predominantly van der Waals. 1 Similar to the sliding between graphite in dry contact, 31 interlayer sliding inside multiwalled carbon nanotubes ͑MWNTs͒ exhibited superlubricity due to the socalled incommensurate contact, 32 bringing down the shear strength to as low as 0.05 MPa when the shell structure was defect-free. 24,26 The major energy dissipation mechanism was believed to arise from the interaction of the open end of outer tubes ͑where dangling bonds and defects were present͒ with the inner shells.…”
Section: Introductionmentioning
confidence: 99%
“…When two incommensurate surfaces are in sliding contact, superlubricity or a state of extraordinarily low friction can occur. Hirano & Shinjo (1990) were the first to suggest that the interaction potential between two surfaces, V AB , could be reduced by making the surfaces incommensurate. Subsequent experiments examined the friction between muscovite mica sheets as a function of lattice misfit angle revealed that the friction was anisotropic and displayed periodicity consistent with the hexagonal symmetry of mica (Hirano et al 1991).…”
Section: Friction Of Crystalline Surfaces (A ) Friction Of Diamondmentioning
confidence: 99%